Analysis of the Effectiveness of Utilizing Canva Education Application in Developing Interactive Learning Media for Early Childhood Education Teachers in Bekasi Regency - Rachmasari Aulia; Pujiarto; Nina Afrianti; Nurhasanah; Iis Ismawati; Erma Catur Wulansari; Maimunah; Nurhasanah (International Conferences on Early Childhood Education Proceedings, 2024)
The ability to develop interactive learning media for the learning process is really needed, including PAUD teachers. Because during the early childhood learning process, abilities are needed that can make the learning process interesting and fun. One technology that can be utilized to improve the ability to develop interactive learning media is the Canva for application. For this reason, a research was carried out which aimed to see how effective the use of the Canva for Education application was in improving the ability of PAUD teachers to develop interactive learning media. This research uses qualitative descriptive research with research subjects being PAUD teachers in Bekasi Regency with a population of 91 people and a sample size of 10 people. Research was carried out using Observation, Interview and Documentation techniques. The research results show that effective use of the Canva for Education application increases the ability of PAUD teachers in developing interactive learning media.